Systemic RALA/iNOS Nanoparticles: A Potent Gene Therapy for Metastatic Breast Cancer Coupled as a Biomarker of Treatment - Cian M. McCrudden; John W. McBride; Joanne McCaffrey; Ahlam A. Ali; Nicholas J. Dunne; Vicky L. Kett; Jonathan A. Coulter; Tracy Robson; Helen O. McCarthy (Elsevier, 2017)
This study aimed to determine the therapeutic benefit of a nanoparticular formulation for the delivery of inducible nitric oxide synthase (iNOS) gene therapy in a model of breast cancer metastasis. Nanoparticles comprising a cationic peptide vector, RALA, and plasmid DNA were formulated and characterized using a range of physiochemical analyses. Nanoparticles complexed using iNOS plasmids and RALA approximated 60 nm in diameter with a charge of 25 mV. A vector neutralization assay, performed to determine the immunogenicity of nanoparticles in immunocompetent C57BL/6 mice, revealed that no vector neutralization was evident. Nanoparticles harboring iNOS plasmids (constitutively active cytomegalovirus [CMV]-driven or transcriptionally regulated human osteocalcin [hOC]-driven) evoked iNOS protein expression and nitrite accumulation and impaired clonogenicity in the highly aggressive MDA-MB-231 human breast cancer model. Micrometastases of MDA-MB-231-luc-D3H1 cells were established in female BALB/c SCID mice by intracardiac delivery. Nanoparticulate RALA/CMV-iNOS or RALA/hOC-iNOS increased median survival in mice bearing micrometastases by 27% compared with controls and also provoked elevated blood nitrite levels. Additionally, iNOS gene therapy sensitized MDA-MB-231-luc-D3H1 tumors to docetaxel treatment. Studies demonstrated that systemically delivered RALA-iNOS nanoparticles have therapeutic potential for the treatment of metastatic breast cancer. Furthermore, detection of nitrite levels in the blood serves as a reliable biomarker of treatment. Keywords: nonviral gene therapy, nitric oxide, nanoparticle, breast cancer, metastasis